Understanding Turkey's Kurdish question - Bilgin, Fevzi; Sarıhan, Ali (Lanham, Maryland : Lexington Books, 2013)
This volume, comprising chapters by leading academics and exports, delves into the complicated nature of Turkey's Kurdish issue. The volume discusses the evolution of Kurdish nationalism, the contemporary Kurdish movement and its violent legacy, civil society efforts in Turkey's Kurdish region, and the international dimensions of the Kurdish question.
Early Kurdish "nationalists" and the emergence of modern Kurdish identity politics: 1851 to 1908 / Djene Rhys Bajalan -- The Kurdish issue in Turkey: its social, political, and cultural dimensions / Oral Çalişar -- The "Kurdish question" revisited: modernity, nationalism, and citizenship in Turkey / E. Fuat Keyman and Umut Özkirimli -- On Turkey's Kurdish question: its roots, present state, and prospects / Cengiz Çandar -- The multifaceted Kurdish movement in Turkey / Michael M. Gunter -- The two periods of the PKK conflict: 1984-1999 and 2004-2010 / Ali Sarihan -- Ending ceasefires for political survival: the use of diversionary strategies by the PKK leadership / Kiliç Buğra Kanat -- Turkey and the democratic opening for the Kurds / Hugh Pope -- Explaining Turkey's failure to develop a political solution for the Kurdish problem / Gökham Bacik and Bezen Balamir Coşkun -- Revitalization of Kurdish Islamic sphere and revival of Hizbullah in Turkey / Mustafa Gürbüz -- The Hizmet movement and the Kurdish question / Doğan Koç -- Turkey's Kurdish question, the United States, and Europe: historical perspective / H. Akin Ünver -- International dimensions of the Kurdish question in Turkey / Joshua W. Walker.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Kurdish question -- Turkey; Kurds -- Turkey -- History; Kurds -- Turkey -- Politics and government; Kurds -- Turkey -- History -- Autonomy and independence movements; Turkey -- Ethnic relations; Asie Mineure -- Relations interethniques; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Minority Studies; Ethnic relations; Kurdish question; Kurds; Kurds -- Autonomy and independence movements; Kurds -- Politics and government; Turkey; History